Potential Development of Tourism Village in Hendrosari Village, Menganti District, Gresik City - Heri Cahyo Bagus Setiawan; Aries Kurniawan; Muhammad Ghufran Ramdhani; Ragillia Ragillia (OJS Universitas Muhammadiyah Gresik, 2020)
The PKM program that is a partner is Hendrosari Village, Menganti District, Gresik City. Villages that have the potential to be developed into tourist villages. The vast land and other economic potentials seem to have been built by this village. However, this potential is not yet optimal in practice. Because through this PKM program we focus on renewing, and some training related to maximizing the potential of villages that become tourist villages. Based on observations and results of field interviews, there are two issues considered by partners namely; 1) not yet optimal knowledge of village communities who are members of the Village Economic Business Group (KUEMDes) related to the potential that exists in the village as a tourist village; 2) Movement of community economic activities in the form of economic business is still in the arrangement of (traditional) home management yet not oriented to agro-industry and siwalan agro-tourism which actually has great potential as an agro-industrial and agro-tourism village. In this PKM program we try to provide alternatives and solutions that provide modern and agro-based business support by providing seminars and workshops related to agro-based business management, change management (change from traditional culture to modern culture in the management of business management. It is expected that the existing potential can be optimized in increasing the economic efforts of the community through agro-tourism based KUEMDes and the use of technology that produces potential resources that can become a source of income for rural communities. This activity was created successfully in the form of creating successful collaborative programs until the end of the PKM, building a family atmosphere between the different and solving problems related to shared problems so that they can be used together to find solutions and find out how to increase the economic benefits of this village if used moderately based on agro-industry and siwalan agro-tourism, of course the hope is to achieve the expected benefits, namely increased knowledge, increased productivity and competitiveness, independence and welfare of the community through the utilization of the potential of villages as lontar tourism villages. Keywords:development, village potential, tourism village